Effects Of Individual, Job And Organizational Characteristics On Personal Innovativeness - Moi, Kok wah (2010)
In addressing the personal innovativeness lacuna of innovation research, an antecedent model was derived from other areas of management. The model hyphothesises that individual, job and organizational characteristics affect the personal innovativeness of knowledge workers.